Multinational versus national firms on capital adjustment costs: A structural approach - Athanasios Lapatinas (Kiel Institute for the World Economy (IfW), 2015)
This paper provides a different perspective on the firm-level empirical analysis of the relation between foreign ownership and capital demand adjustment in host countries. The author estimates a dynamic structural model of investment on a sample of 4672 Belgian firms observed between 2003 and 2010 that permits to distinguish the 'ownership status' of firms. He considers a dynamic discrete choice model of a general specification of adjustment costs including convex and nonconvex components. He uses the method of simulated moments procedure to estimate the structural parameters. The results indicate that multinational's affiliates face lower capital adjustment costs than national firms.
Keywords: F23; D24; D92; G31; 330; Multinational Firms; Investment; Capital Adjustment Costs